Technical inspection of buildings and construction: modern approaches and solutions - Hryhorovsky, A.; Murasyova, O.; Bronevytskyi, A. (Ways to Improve Construction Efficiency, 2023)
In this article, the authors try to outline modern technological solutions that are used in the practice of performing technical inspections of buildings and structures, as well as to analyze the leading technological achievements in the theory of performing these works. During the last year, as a result of military actions caused by the aggression of the Russian Federation, about 150 thousand buildings and structures were destroyed or damaged in Ukraine, including more than 17.5 thousand multi-apartment residential buildings. Damaged buildings and structures require a technical inspection to determine their further repair, reconstruction or controlled dismantling and new reconstruction. In Ukraine, the process of restoring damaged social, economic and residential buildings is already underway. Monitoring and periodic inspection of the condition of restored buildings are important parts of the facility management system, as it allows timely detection and response to any damage or deviations from normal functioning, which can ensure safety and extend the service life of the structure. The scope of work on technical inspection and their special conditions determine the need for effective performance of work with the possibility of applying modern approaches and solutions. Information is given about the main authors of scientific research on this topic, the names of foreign companies that are the drivers of the market of modern building inspection technologies are indicated. The main commonly known methods of inspection of buildings and structures are analyzed, their types are systematized. Among modern technologies, the main attention is paid to the use of unmanned aerial vehicles, as such, which have become widespread in the developed countries of the world. The advantages of using this technology are indicated, as well as the problems accompanying the practical commercial use of unmanned aerial vehicles during the technical inspection of buildings. Prospective topics for further research in this field of science are proposed, in particular, to develop a methodology for the economic feasibility and effectiveness of using one or another innovative method of examination.